Age Estimation by Modified Demirjian's Method in Children and Adolescents of Hyderabad Population-A Panoramic Study - M. Priyanka; G. Kiran; R. Poornima; R. Shravani; K. C. Shobhita; P. Preethi (Wolters Kluwer Medknow Publications, 2018)
Introduction: Human identification is one of the most important tasks of forensic practitioner. Estimation of age is one of the essential factors which play a significant role in each aspect of life, including forensic medicine and dentistry, wherein race, age, and sex determination are used in person identification. Aims and Objectives: To correlate the relationship between chronological age (CA) with dental age (DA) using modified Demirjian's method and to establish the applicability of modified Demirjian's method in Hyderabad population. Materials and Methods: Our study samples consist of 113 randomly selected samples (39 males and 74 females) of age ranging from 8 to 20 years of Hyderabad population for children and adolescents. Panoramic radiographs of these patients were evaluated based on the modified Demirjian's method. The obtained data were tabulated and analyzed using SPSS version 20.0. Results: The present study showed a significant correlation between CA and DA in both females (r = 0.84) and males (r = 0.882). The overall mean difference between the DA and CA for females and males was +1.14 and +0.86, respectively. In the whole sample, DA was found to be over estimated by +1.04 with CA. Conclusion: DA overestimated the CA by +1.04 years. According to the present study, there was a difference and overestimation of DA in comparison with CA in Hyderabad population and hence population specific formula for each area is necessary.